Pelatihan Standar Akuntansi Keuangan Entitas Privat pada Guru – Guru Sekolah Menengah Kejuruan dan Dosen Akuntansi - Zabidi, Imran; Mulyati, Ade; Suryono, Dwi Windu; Hendra, Lim (PROGRESIF: Jurnal Pengabdian Komunitas Pendidikan, 2024)
The Financial Accounting Standards Board has made changes to the Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP) with the Financial Accounting Standards for Private Entities (SAK EP), this change is a significant change because all statements in the SAK ETAP standard have been changed and refer to the Financial Accounting Standards (SAK) in 2012. This change was made because of the large differences between SAK ETAP and general SAK which could have a significant impact on fair value measurement and consolidation treatment if there is a private entity that is consolidated with an entity that uses general SAK. This training was attended by 10 participants from Accounting Vocational High School teachers and college lecturers in the field of accounting.